PERANAN SEKTOR PERTANIAN DALAM PEREKONOMIAN DAN PENYERAPAN TENAGA KERJA DI PROVINSI GORONTALO - Mohamad Arif Novriansyah Biki; Grace A. J. Rumagit; Charles R. Ngangi (Sam Ratulangi University, 2016)
This research aimed to analyze the role of agricultural sector to analyze in the economy and labor Absorption in Gorontalo Province. This research was conducted over three months and started from June to August 2015 in Gorontalo Province. The data used in this research was secondary data which was obtained from Statistics Central Bureau of Gorontalo Province. The analysis used analysis of Location Quotient (LQ), Multiplier Short Run (MS), elasticity of labor, and Trend Linear by using the PDRB variable and numbers of labor force. The result of this research showed that the role of agricultural sector in the absorption of labor in Gorontalo Province is relatively stable in each year, and reviewed from PDRB terms the agricultural sector including the basis sector. Therefore, it needed continuing research to know factors which influence PDRB except the labor, which can increase PDRB of agricultural sector. Furthermore, the role of agricultural sector in absorption labor in Gorontalo Province is big enough and relatively stable in each year. Reviewed from PDRB aspect and labor aspect, agricultural sector was including the basic sector. Government of Gorontalo Province was expected to give more concern by increasing of investment and improving of human resources in agricultural sector.Key words: Agricultural Sector, Location Quotient, Multiplier Share, Elasticity of Labor, Trend Linear.